PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI LINGKUNGAN BIRO HUMAS DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI SUMATERA SELATAN - Tutik Pebrianti (Politeknik Negeri Sriwijaya, 2013)
Employees is one of the most important factors in achieving the goals of an organization or institution, because the technology is perfect when it is not supported by qualified human resources, the company will not be able to run properly. As a driver of human resources to work more optimally is motivation, agencies should provide motivation to any employee in any form, so that employees can work harder with every ability, aptitude and skills it provides. In line with the company objectives between motivation and demand for the company should be mutually supportive. This means the existence of motivation has given employees the opportunity to become more capable subordinates to develop the skills that employees are expected to be loyalty and discipline in work. The purpose of this research is to analyze the influence of work Discipline variable (X1), Motivation (X2) on Employees Performance variable (Y). The sampling technique used in this study is a total sampling (census). The number of samples has taken in this research about 114 people (100% of the population). All the variables in this research have a positive and significant impact on performance improvement in the Bureau of Public Relations and Protocol Setda South Sumatra Province.